Challenges and solutions for instituting an efficient maintenance program for laboratory equipment in Central Asian, and developing world, countries - Riza Ikranbegiin; George Schmid; David Hoos; Andrew Young; Phyllis Della-Latta; Paul Spearman; Artur Ramos; Bereket Alemayehu; Begaiym Achmetova; Gulzhan Nauryzova; Adilya Albetkova (BMC, 2019)
Abstract We review the current state of quality assurance in laboratories of the five Central Asia Republics (CARs), focusing on laboratory equipment, and compare quality assurance approaches with CLSI standards. The laboratories of the CARs faced exceptional challenges including highly-structured laboratory systems that retain centralized and outmoded Soviet-era approaches to quality assurance, considerably jeopardizing the validity of laboratory tests. The relative isolation of the CARs, based on geography and almost exclusive use of the Russian language, further hamper change. CARs must make high-level government decisions to widely implement quality assurance programs within their laboratory systems, within which approaches to the management of laboratory equipment will be a prominent part.